Using Flipped Classroom Model to Enhance the Junior High School Students’ Achievement and Engagement in Algebra - Mulyani, Wiwik (Pendidikan Matematika STKIP Kusuma Negara, 2022)
This study examines whether using flipped classroom model could enhance junior high school students' achievement and engagement in algebra. A quasi-experimental design which is a switching replication model with posttest only is used in this study to determine whether the students’ achievement in the experimental group (using flipped classroom model) differs from the control group (using traditional classroom model). A questionnaire is used to evaluate the students’ engagement during the lessons in the experimental group, and the results then are presented in the descriptive statistics. The result of this study is that the experimental group has significantly (p-value=0.001) higher gain mean scores (M=61.54, SD=20.49) than those in the control group (M=55.63, SD=23.76). It describes that students in the experimental group have better achievement than the students in the traditional classroom. This study also shows that the students in the experimental group agree that they are more engaged and active during the lesson, with the mean of the items engagement being more than 3,7 (3.72?M?4.19). The correlations between the engagement items and the posttest from flipped classroom show positive, moderately strong correlations. Thus, this study sheds light on flipped classroom models as one of the great teaching models nowadays.